Nanobiomaterials in soft tissue engineering : applications of nanobiomaterials - Grumezescu, Alexandru Mihai (Applications of nanobiomaterials, 2016)
This book brings together recent developments and the latest approaches in the field of soft tissue engineering at the nanoscale, offering a new perspective on the evolution of current and future applications. Leading researchers from around the world present the latest research and share new insights. This book covers the major conventional and unconventional fabrication methods of typical three-dimensional scaffolds used in regenerative medicine. Surface modification and spatial properties are included in an up-to-date overview, with the latest in vivo applications of engineered 3D scaffolds discussed. The book also considers the impact, advantages and future scope of the various methods. This book will be of interest to postdoctoral researchers, professors and students engaged in the fields of materials science, biotechnology and applied chemistry. It will also be highly valuable to those working in industry, including pharmaceutics and biotechnology companies, medical researchers, biomedical engineers and advanced clinicians. --